LSM and DTM-Pade approximation for the combined impacts of convective and radiative heat transfer on an inclined porous longitudinal fin - Wang, Fuzhang; Varun Kumar, R.S.; Sowmya, G.; El-Zahar, Essam Roshdy; Prasannakumara, B.C.; Khan, M. Ijaz; Khan, Sami Ullah; Malik, M.Y.; Xia, Wei-Feng (Case studies in thermal engineering, 2022)
The novel exploration designates temperature variation through an inclined porous longitudinal fine with convective radiative phenomenon. The Rosseland approximation is considered for the radiation heat exchange. Using non-dimensional terms, the existing system of stated problem is reduced to ordinary form. To resolve the nonlinear ordinary system of heat transfer, the analytical approaches, differential transform method (DTM) with Pade approximant has been workout. Furthermore, simulations are developed to examine the outcomes of convincing flow parameters like radiative-conduction parameter, porosity parameter, and conduction-convection variable on the thermal distribution for different modes of heat transfer like nucleate boiling and radiative heat transfer. The results show that an increase in the conduction-convection variable, porosity variable, and radiation number causes a reduction in the thermal field. On the other hand, augmentation change is appeared due to heat generation constant. The thermal behavior of the fin declines with escalating angle.